The Relation of Human Suffering in God's Grace - David Ming (Theological Journal Kerugma, 2019)
Suffering is a legacy of the existence of the world of souls [humans] living on earth. Suffering is not imagination, not some nightmare, on the contrary is real, actual, but not academic. Suffering comes when humans are born. Humans cannot escape suffering. Suffering comes from various angles of life. Suffering comes from a broken relationship with God. Starting from the failure of Adam and Eve's relationship with God, humans began to feel suffering. Humans cannot resist the suffering they experience. The purpose of this study is to determine the cause of human suffering and its consequences, and how to overcome suffering. The author uses a descriptive method of literature and research results as follows: first, mercy is the perfect character of the deity of God. God's mercy from eternal to eternal until humans are afraid of God. Kindness is the essence of the quality of divinity, but God shows mercy on an ongoing basis through His sovereign will. Second, the source of God's mercy. The source of God's mercy is God's goodness and love expressed mysteriously. God's mercy is stated to guide someone to live righteously. People who receive God's mercy are living in godly living conditions and they need God's protection or care. Third, God's mercy cannot be stopped by humans. Instead humans can be made to not understand by God. God is free to act surprisingly, correcting human deviation. God is free to allow the test of Satan and not to tell anyone about it that was tested. God is also free to regulate